Admissions for pulmonary embolism at a tertiary South African hospital - Kirstensamy, Sivaisen Ricardo; Brown, Susan; Moodley, Yoshan (SA Heart Journal, 2018)
Background: Published reports of pulmonary embolism (PE) from South African (SA) settings are rare. We sought to address this paucity in the literature. Methods: This case series (CS) involved 61 adult patients admitted to a tertiary SA hospital over a five-year period with a primary diagnosis of PE. Data related to patient demographics, PE presentation, risk factors, treatment, and inpatient mortality were collected, and then analysed using descriptive statistics. Results: Most of our CS were aged <65 years (86.9%), female (67.2%), and of black African ethnicity (73.8%). Dyspnoea and chest pain were the most common symptoms (86.9% and 41.0%, respectively). Common clinical signs included tachypnea (47.5%) and tachycardia (42.6%). Common established risk factors were cardiac failure (49.2%) and obesity (27.9%). Massive, submassive, and minor PE, was diagnosed in 8.2%, 62.3%, and 8.2% of patients, respectively. Most patients received anticoagulation therapy (95.1%), with thrombolysis and embolectomy performed only in smaller proportions (24.6% and 11.5%) of patients. Inpatient mortality was 23.0%. Most patients who died had submassive PE. Conclusion: We provide a report of PE cases from a SA setting. Our findings have important implications related to the management of PE in SA.